Principles and application of tunnel gravity full-space positioning and detection method for deep high-density vertical orebodies - Wang, Jiyu; Han, Runsheng; Li, Wenyao; Cheng, Ruihong (Frontiers in Earth Science, 2022)
Considering the needs of current deep mineral exploration and development, the tunnel gravity exploration method is advantageous, as it is unaffected by electromagnetic interference, is hardly affected by terrain, has a high detection accuracy, and overcomes the multi-solution problem of geophysical anomalies. Herein, to systematically explain the distribution law and principle of the tunnel gravity method in spatial position prediction, a systematic study was performed on upright orebodies, and 18 types of positive and negative combination rules of spatial distribution anomalies are proposed. The method is used for the detection of concealed ore in the deep part of the Huangshaping skarn-type deposit in southern Hunan, China, and accurate results are obtained. The results indicate that tunnel gravity exploration solves the problem of orebodies located in the deep parts of a high-density vertical orebody when a single tunnel or multiple tunnels are detected. This study not only extends the theory and method of tunnel gravity exploration but also provides an important basis for the layout of deep exploration projects.